Wave-induced reconfiguration of and drag on marsh plants. (January 2021) - Zhang, Xiaoxia; Nepf, Heidi
Abstract: Salt marshes are a common feature in coastal regions and have been noted for their ability to attenuate wave energy, providing an important first line of coastal defense. Marsh plants usually consist of multiple leaves distributed along a central stem. This paper constructed a model predicting wave force on a marsh plant by modeling the reconfiguration of both the leaves and stem in waves. The individual leaf and stem models and the full plant model were validated with experimental measurements of drag and plant motion using both live and dynamically-similar model plants under a range of wave conditions. Although the leaves exhibited greater reconfiguration than the stem, they contributed more than 70% of the plant drag. Plant reconfiguration produced a drag force that had a weaker than quadratic dependence on wave velocity. A simplified model, which combines scaling laws for the stem and individual leaves, is proposed and validated. Wave drag on a variety of marsh species with different morphology and rigidity were estimated and compared.